EPIDEMIOLOGI MEROKOK PADA SISWA KELAS 7 DAN 8 SMPN 33 KOTA PEKANBARU - Alamsyah, Agus; Susanti, Nurvi (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2017)
Epidemiology smoke are of science that studies distribution, the frequency and determinan someone or some group to behave smoking. Interviews with any one teacher SMPN 33 Pekanbaru say a lot of their students who company to smoking habit good students men and women. Research aims to know the proportion and determinan to behavior smoked on the students SMPN 33 Pekanbaru. Research is quantitative analytic with design cross-sectional. Population is the class 7 and 8 smpn 33 the City of Pekanbaru were 324 people with sample the total population. The results of the study obtained that the proportion of students who smoke in SMPN 33 the City of Pekanbaru is it was found that 89 people (27.5%) of 324 people. Variable knowledge on smoking (p=0,000), cigarette advertisement (p=0,009), family smoking (p=0,022) their peers smoking (p=0,009) and cigarette advertisement (p=0,001) related to behavior smoking students SMPN 33 the City of Pekanbaru .knowledge , cigarette advertisement , family smoking , their peers smokers and pocket money is determinan behavior smoking students SMPN 33 the City of Pekanbaru.